2018
DOI: 10.3390/nu10111655
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Association between n-3 Long-Chain Polyunsaturated Fatty Acid Intake and Depressive Symptoms: A Population-Based Cohort Study in Japan

Abstract: It remains unclear whether n-3 long-chain polyunsaturated fatty acids (LCPUFA) have a preventive effect on depression in the general population. This study investigated the longitudinal association between n-3 LCPUFA intake and depressive symptoms in community-dwelling Japanese participants. The participants were aged 40–79 years at baseline in the cohort study, wherein examinations, including the assessment of depressive symptoms and nutritional status, were biennially conducted from 1997 to 2012. The subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 56 publications
(71 reference statements)
4
23
0
3
Order By: Relevance
“…Our findings about n-3 fatty acids intake are consistent with other studies, including cross-sectional [18,23,24], prospective cohort [17,[25][26][27], meta-analysis [19,28] and experimental studies [20]. The results from a cross-sectional study [23] indicated that higher n-3 fatty acids intake was inversely associated with the risk of evaluated depressive symptoms.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings about n-3 fatty acids intake are consistent with other studies, including cross-sectional [18,23,24], prospective cohort [17,[25][26][27], meta-analysis [19,28] and experimental studies [20]. The results from a cross-sectional study [23] indicated that higher n-3 fatty acids intake was inversely associated with the risk of evaluated depressive symptoms.…”
Section: Discussionsupporting
confidence: 90%
“…The results from a cross-sectional study [23] indicated that higher n-3 fatty acids intake was inversely associated with the risk of evaluated depressive symptoms. Chika Horikawa et al [27] also found the protective effect of n-3 fatty acids on depression through an established cohort. Moreover, a recent meta-analysis [19] explored the dose-response relationship between n-3 fatty acids and depression, and a reverse J-shaped effect was found.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…One of the major reasons we did not find associations between plasma phospholipid n-3 PUFAs and MDD risk might be due to the ceiling effect of n-3 PUFA intake. In fact, if we look closely at the difference in mean baseline intake of n-3 PUFAs between the present study 9 and the abovementioned Japanese study 13 , it is about 0.5 g/day (3.0 g/day vs. 2.5 g/day 38 , respectively). Individuals with lower dietary intake of n-3 PUFAs are much more likely to see clinical benefits of additional n-3 PUFA intake than those with higher intake 39 .…”
Section: Discussionmentioning
confidence: 54%
“…A two-month, randomized, double-blind, placebo-controlled trial revealed that omega-3 PUFA supplementation reduced the occurrence of depressive symptoms in elderly females [10]. Moreover, a longitudinal cohort study showed that high intakes of EPA and DHA reduced the risk of depression in middle-aged Japanese men and women [11].…”
Section: Introductionmentioning
confidence: 99%